A medico-legal examination of homosexual women and their children : ethical consideration and the role of the clinical psychologist - Tucker, Cherón (1986)
Bibliography: leaves 250-284.Past and present legal and medical proscriptions towards female homosexuality were reviewed, and the role of the women's movement and gay liberation organisations were considered in effecting social change. The legal predicaments of homosexual mothers seeking child custody was noted and the concerns of the court outlined and used to organise a comprehensive review of the literature on aetiology, personality adjustment, psychiatric status, life style and mothering capabilities of gay women. The effects on children raised by a homosexual mother were evaluated and it was noted that this experience cannot be separated from the child's experience of the effects of divorce and absent fathering amongst other things. A case study was presented, and the concerns of the court were found to be generally unwarranted and most difficulties experienced by the child seemed to be secondary problems relating to social prejudice and stigmatization. Ethical considerations were documented concerning the role of the psychologist in terms of social reform, research, community involvement, modes of therapy, legal reform and child custody disputes. Future directions were considered